The assessment of language restrictions in abstracts of systematic reviews in dentistry: A meta-research study - Tatjana Lörscher; Naichuan Su; Clovis Mariano Faggion (PLoS ONE, 2025)
Background The adequate interpretation of findings in systematic reviews can be affected by the lack of information on the language of the examined studies. The study sought to assess the reported information on restrictions set on the language of primary studies examined in systematic reviews published in dentistry. The study also investigated associations between the characteristics of the systematic reviews and language restrictions. Methods A comprehensive search was conducted in the Web of Science database for systematic reviews in the field of dentistry. Abstracts published from the inception of the database up to 24 February 2023 were included and relevant information was extracted. Only abstracts published in English were included. Logistic regression analyses were performed to examine the association between the characteristics of the systematic reviews and the presence of language restrictions. Additionally, a random sample of 9.2% of the full texts was reviewed to identify differences in the reporting of language restrictions between the abstract and the full texts. Results A total of 3922 abstracts were initially retrieved, and 3465 abstracts were included in the analysis based on the eligibility criteria. Approximately 79% (2739) did not report any language information. Only 7% (238) of the abstracts declared no language restrictions in the primary studies selected. Meta-analysis conducted, journal type, reporting of primary study design, actual number of words in abstracts and the country and continent of first authors affiliation were statistically significantly associated with language restrictions of the systematic reviews. However, the absence of information about language restriction appears to be a poor indicator of reporting or not language restriction in the full-text of the article. Conclusions Abstracts of systematic reviews in dentistry frequently underreport language restrictions applied to the primary studies examined. Various characteristics of systematic reviews are significantly associated with these restrictions, highlighting inconsistencies in reporting practices.